The value of context in determining the sustainability and effectiveness of feedback practices in higher education: a case study of a general education program - Buchanan, Jaime (My University, 2025)
This evaluative case study investigated the situated feedback practices of a prescribed general education program at a university in the Middle East. It examined the extent to which the feedback practices on this program could be considered effective and sustainable as evidenced by the extant feedback literature in higher education. To facilitate this, the study employed a qualitative design and utilized a dual theoretical framework. First, the study interrogated feedback practices from a socioconstructivist or sociocultural perspective, since this is the educational paradigm upon which the program is premised. Second, it investigated feedback practices from a sociomaterial lens, in order to reveal the influence of non-human actors such as technology, time, and space on feedback. Data were collected using document analyses from institutional policies and other records associated with semester-specific course-related documents, faculty interviews, and an object interview with the bespoke learning management system (LMS). Purposive sampling was utilized, and data were collected and analyzed iteratively using reflexive thematic analysis. The study found that the feedback practices of the program under investigation were neither effective nor sustainable from a socioconstructivist perspective due to a lack of alignment with three foundational aspects of sociocultural theories of learning: active student positioning, opportunities for scaffolding, and culturally situated interactions. Further, the sociomaterial analysis revealed that non-human actors significantly shaped feedback practices, constraining the modality, timing, and focus of feedback information. In particular, this analysis found that the LMS exerted powerful influence on faculty feedback practices through many of its design features and data analytics. Ultimately, the study concluded that the feedback practices of the general education program were found to be more aligned with technocratic views of education that prioritize managerialism and accountability over teacher professionalism and agency out of a concern for upholding the “science of learning”. These findings highlight the need for institutions to critically evaluate the purpose and place of feedback in program design and delivery, and how their technological infrastructure shapes pedagogical practices, with implications for LMS design, faculty agency, and institutional policies that govern feedback in higher education contexts.
Keywords: Feedback; Higher education; Sustainable feedback; Socioconstructivist feedback; Sociomaterial feedback; Learning management systems